Homeopathic treatment in oral lichen planus control: Case Report - Wastner, Rafaela Savio Melzer B. F.; Zanferrari, Fernando Luiz; Sassi, Laurindo Moacir (Journal of Oral Diagnosis, 2017)
Lichen planus, considered an inflammatory disease of the stratified squamous epithelium of unknown aetiology, is a condition that often affects the oral mucosa. This pathology is more prevalent in female caucasian patients and the signs and symptoms range from asymptomatic to completely debilitating painful mucosal lesions. Objective: To report a case of a patient affected by lichen planus, whose treatment was homeopathic. Case report: Female patient with pain complaints in oral mucosa and presence of whitish plaques in bilateral buccal mucosa that exacerbate during periods of stress. The lesions were controlled by homeopathy medication, which leaded to regression of the lesions and provided comfort to the patient. Conclusion: The use of homeopathy in Dentistry is a new concept, which has been growing and proving to be effective, especially when related to autoimmune diseases, where the stress is a factor linked to the development/ exacerbation of the signs and symptoms.